Centrifuges for Microgravity Simulation. The Reduced Gravity Paradigm - van Loon, Jack J. W. A. (Frontiers in Astronomy and Space Sciences, 2016)
Due to the cumbersome nature of performing real microgravity - spaceflight research scientists have been searching for alternatives to perform simulated microgravity or partial gravity experiments on Earth. For more than a century one uses the slow rotating clinostat as developed by von Sachs at the end of the nineteenth century. Since then, the fast rotating clinostat, the 3D clinostat or the random positioning machine, the rotating wall vessels, tail suspension and bed rest head down tilt and lately the levitating magnets have been introduced. Several of these simulation systems provide some similarities of the responses and phenotypes as seen in real microgravity experiments. However, one should always realize that we cannot reduce gravity on Earth, other than the relative short duration free fall studies in e.g. drop towers or parabolic aircraft. In this paper we want to explore the possibility to apply centrifuges to simulate microgravity or maybe better to simulate hypo-gravity. This Reduced Gravity Paradigm, RGP is based on the premise that adaptations seen going from a hypergravity level to a lower gravity are similar as changes seen going from unit gravity to microgravity.